Public Attitudes toward people with mental illness in a Global Perspective: A Scoping Review - Rahmawati Rika; Somantri Irman (Jurnal Keperawatan Florence Nightingale, 2026)
The high prevalence of mental disorders is not accompanied by an equal level of public acceptance. Stigma and negative attitudes toward people with mental disorders remain barriers to recovery and social integration. This study aimed to identify public attitudes and influencing factors through a scoping review. Articles were collected from Scopus, SpringerLink, ScienceDirect, and Sage Journals using a PCC framework–based search strategy. From 145,241 articles, 12 met the inclusion criteria and were analyzed narratively. Results: public attitudes are influenced by culture, education, age, gender, mental health literacy, and personal experience. Negative attitudes include the perception that people with mental disorders are dangerous or need strict control. Positive attitudes appear in those with better mental health literacy and direct experience. Stigma also affects families through stigma by association. Conclusion: public attitudes are complex and contextual. Multidisciplinary efforts in public education, healthcare training, and family support are needed.